PENGARUH SIKAP UTILITARIAN DAN SIKAP HEDONIS TERHADAP MINAT BELI PRODUK BRANDED BEKAS DI SURAKARTA - Dendyto Daniel Lafrinda; Anton Agus Setyawan (Universitas Sarjanawiyata Tamansiswa, 2024)
Many types of clothing models create a feeling of desire for ownership among consumers, even though used clothing and frugal lifestyles are also increasingly being implemented in society around the world. Thrifting has become an important trend because it offers individuals an alternative to fulfill their fashion needs and desires. This surge in popularity has given thrift stores a boost, creating a sustainable market for used clothing. This increasing trend is expected to continue, with projected total product sales in 2022. This study aims to test utilitarian behavior on the desire to buy and provide an evaluation of luxury lifestyles on the desire to buy. This study uses a quantitative type with clear and focused calculations, this study was conducted with the main focus being Solo Raya students, the way to collect respondents was purposive sampling. Adopted from a study by Malhotra (2006:291), the questions asked must have a sample of 10 x or at least 5 x the questions, the sample calculation was carried out and found 90 respondents. This study uses main data with results using a questionnaire whose scale is Likert. Data findings were processed using the SPSS program. The findings of this study are that utilitarian behavior has a positive and significant impact on the desire to make a purchase. Luxury lifestyle behavior has a positive and significant impact on the desire to make purchases.